The Application of Sanctions to Correctional Inmates for Disciplinary Violations - Abid Nur Fariz Pamungkas; Endang Sutrisno; Harmono (Riviera Publishing, 2026)
This research aims to analyze the implementation of sanctions against Correctional Inmates (WBP) who commit disciplinary violations at the Class IIB Correctional Institution in Majalengka, based on the Regulation of the Minister of Law and Human Rights Number 8 of 2024 concerning the Implementation of Security and Order in Correctional Work Units. The research method employed is normative juridical, using a statutory approach and analysis of primary and secondary legal materials, supported by empirical field data. The findings indicate that common disciplinary violations include the possession of communication devices (mobile phones), the possession of sharp weapons, acts of violence among inmates, and debt practices that potentially disrupt security and order within the correctional institution. Sanctions for these violations are imposed in the form of light, moderate, and severe disciplinary measures, including placement in isolation cells, transfer to other correctional institutions, and recording in Register F, which results in the loss of certain rights such as remission and integration programs. The imposition of sanctions is carried out through an examination mechanism by the investigation team and the Correctional Observer Team, while upholding the principles of proportionality, justice, and equality before the law. The challenges encountered include overcrowding, limited human resources, and inadequate supporting facilities and infrastructure. Therefore, enhanced supervision, additional personnel, and the optimization of facilities are required to support the effectiveness of disciplinary sanctions and to ensure security and order within correctional institutions.